Structural requirements of research tissue banks derived from standardized project surveillance - Herpel, Esther; Koleganova, Nadezda; Schreiber, Barbara; Walter, Britta; Kalle, Christof von; Schirmacher, Peter (Virchows Archiv, 2012)
Tissue banks constitute decisive and rate-limiting resource and technology platforms for basic and translational biomedical research, notably in the area of cancer. Thus, it is essential to plan and structure tissue banking and allocate resources according to research needs, but essential requirements are still incompletely defined. The tissue bank of the National Center of Tumor Diseases Heidelberg (NCT) was founded with the intention to provide tissues of optimal quality and to prioritize the realization of research projects. We analysed its structure and prospective project management registration as well as tracking records for all projects of the NCT tissue bank as of its start in 2005 in order to obtain information that may be relevant for tissue bank planning. All project proposals submitted to the NCT tissue bank (n = 681) were included in the study. For a detailed evaluation of provided services, only projects that were completed until July 2011 (n = 605) were analysed. For these 605 projects, NCT tissue bank provided 769 specific services. In all projects/services, we recorded project leader, type and amount of material provided, type of research (basic/translational), work load of project and project completion. Furthermore, all completed projects were tracked after 90 days according to a standard protocol to determine principal investigators’ (PI) satisfaction and quality of the provided material. Until July 2011, 605 projects had been successfully completed as documented by material transfer agreement. Of the projects, 72.7 % addressed basic research, 22.3 % were translational research projects and 3 % concerned epidemiological research; 91 % (n = 546) concerned a single PI and the NTC tissue bank. For these projects, 769 specific services were provided. Of these services, 288 concerned providing formalin-fixed and paraffin-embedded (FFPE) tissue (extracts, full size sections), 126 providing fresh frozen materials (including fresh frozen sections), 137 providing tissue micro-array (TMA)-based sections and 199 providing immunohistochemical services. Project tracking demonstrated that all projects had started within 90 days after reception of the material by the PIs, and PI satisfaction with provided material exceeded 97 %. Standardized registration and tracking provides valuable structural information for planning and financing of tissue banks and allocation of resources. The high number of completed projects as well as high user satisfaction demonstrates that structuring of tissue banks should be preferably research-oriented and highly efficient. The comparable number of requests for FFPE and fresh frozen tissue as well as TMA-based services underpins the need for a broad approach in terms of methods and material types in order to fulfil research needs.